Application and Interpretation of Resonance Frequency Analysis in Auditory Osseointegrated Implants: A Review of Literature and Establishment of Practical Recommendations. Issue 9 (October 2015) - Nelissen, Rik C.; Wigren, Stina; Flynn, Mark C.; Meijer, Gert J.; Mylanus, Emmanuel A. M.; Hol, Myrthe K. S.
Abstract : Objective: To establish standardization of implant stability measurements in auditory osseointegrated implants by means of resonance frequency analysis (RFA) through reviewing the currently published literature. Methods: Studies reporting on RFA in auditory osseointegrated implants were identified, and the outcomes and the way these were reported were evaluated. Results: Thirteen clinical studies reporting RFA outcomes of auditory osseointegrated implants were identified and analyzed, which demonstrated variations in methodology and reporting of data. The different reporting standards made a meta-analysis impossible. Heterogeneity and limitations were found in reporting of the types of implants, abutments, and SmartPegs used; study population sizes; follow-up duration; and, reporting of the implant stability quotient (ISQ). Conclusion: RFA is an interesting outcome of clinical studies on auditory osseointegrated implant research and might have potential as a clinically relevant tool for assessing implant stability. Because of the heterogeneous data that have been reported to date, the following guidelines for standardization of application and reporting were established. The implant and abutment type and length, and the type of SmartPeg should always be stated. Absolute stand-alone ISQ values should not be interpreted individually. ISQ values are at this moment most meaningful as a trend in the individual patient or in a population over time. No conclusions should be based on individual ISQ values. Standardized time points for RFA in research should be determined prospectively, with surgery as a baseline. After abutment replacement, individual ISQ trends from baseline cannot be interpreted anymore if the abutments differ in length.